TINJAUAN YURIDIS PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM DALAM MEWUJUDKAN NEGARA KESEJAHTERAAN BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2012 - Ade Millatus Sa'adiyyah (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2023)
ABSTRACT Land is indispensable for human, such as residence, and another infrastructures. A constrain on face is continuous population growth while lard availability is limited. Indonesia currently being actively implementis development, it goals are creating prosperity and justice for Indonesia citizen. In order to implement it, demand for lard is increasing. In development activities related to the lard reguirement, could appears the various cortlictirs interests. If the land was taken for development purpose it must sacrifice the interests and contrary to human right and state law. Yet, if there is no land, the goals of development to create state welfare and justice is hampered. The aims this thesis to solve some problems, are : (1) How to acguisihor ofland development as set out in law No 2, 2012 about land procuremenr for grouth on public interest in line with country goals such as increasing society welfare? (2) Does law No 2, 2012 about land acguisihor for growth on public interest in practice in line with human right? (3) How the land acguisition perpective for growth on public interest in future to realize welfare state?To answer this problems, pursued through juridic normative approach method in which to analyze according to law and regulations associated with empirical data, and find conclusions ther arrange a descriptive to find the answer to the problems.The study showed that : (1) Land acguisition for development on public interest set in law No 2.2012 there is lack in indemnity. (2) Law No.2, 2012 in practice should accordance with the human right. Human right mears property rights to land then taken by the state for public development must be accordance with article 2, said that principles and purposes of the implementation of the land acguisition including the principle of humanity. (3) Law No 2.2012 expected that agrarian law in future better than previous regulations for government as land acguisition operator, also for the party whose land is used for public interest and realize welfare for all Indonesia society.